Let S n = ( x n + x n 1 ) .
Now ( S 3 + S 1 ) ( S 7 + S 1 ) ( S 1 1 + S 1 ) = ( S a + S 7 ) ( S b + S 7 ) ( S c + S 7 )
If the equation above is always true then find the value of ( a + b + c ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Mine solutions are not just same but identical to you:)
Voted up. My method now is too long .
Sir how could u prove this..................please send
( S 7 + S 1 ) = ( S 1 + S 7 ) i s a l l r e a d y t h e r e . s o a = 1 ∴ ( S 3 + S 1 ) ( S 1 1 + S 1 ) = ( S 2 ∗ S 1 ) ( S 6 ∗ S 5 ) = ( S 1 ∗ S 6 ) ( S 2 ∗ S 5 ) = ( S 5 + S 7 ) ( S 3 + S 7 ) s o b = 5 , c = 3 . a + b + c + 1 + 5 + 3 = 9 .
Problem Loading...
Note Loading...
Set Loading...
Again applying the beautiful property, S i S j = S i + j + S i − j ⇒ ( S 3 + S 1 ) ( S 7 + S 1 ) ( S 1 1 + S 1 ) = ( S 1 S 2 ) ( S 3 S 4 ) ( S 5 S 6 )
= ( S 1 S 6 ) ( S 2 S 5 ) ( S 3 S 4 ) = ( S 5 + S 7 ) ( S 3 + S 7 ) ( S 1 + S 7 ) ⇒ a + b + c = 5 + 3 + 1 = 9